Do Migration Characteristics Influence the Utilization of Basic Public Health Services in Internal Elderly Migrants in China? - Lin, Yanwei; Wang, Tingxian; Zhu, Tingting (Frontiers in Public Health, 2021)
Background: The literature shows that migratingion characteristics isare thea potential pathway through which migration can influence basic health care services utilization. The goal is to explore the effect of migration characteristics on the utilization of basic public health services for internal elderly migrants in China and to identify the pathways that might promote their utilization of basic public health services. Methods: We studied 1544 internal elderly migrants. The utilization of basic public health services was determined by participating in the free health checkup organized by community health service institutions in the past year. Migration characteristics were represented by years of residence and reasons for migration. Other variables included demographic characteristics and social factors, e.g., the number of local friends and exercise time per day were measured for to represent social contacts. Multivariate binary logistic regression was employed to explore the association of the variables with the likelihood of using community health services. Results: A total of 55.6% of respondents were male, and the mean age was 66.34 years (SD, 5.94). A low level of education was observed. A total of 59.9% of migrants had residence times over 10 years, and the main reason of for migrating was related to family. Of these migrants, 12.9% had no local friends. Furthermore, 5.2% did not exercise every day. Social contacts were complete mediators of the impact of migratingon characteristics on their utilization of primary health care. Conclusion: Our study highlighted the mediationng role of social factors in the relationship between migration characteristics and the utilization of basic public health services among Chinese internal elderly migrants. The findings supported the need to increase the opportunities of social contacts between local elderly individuals and internal elderly migrants.